Variables Associated with Adherence to Stress Ulcer Prophylaxis in Patients Admitted to the General Hospital Wards: A Prospective Study - Shadi Farsaei; Sajad Ghorbani; Payman Adibi (Tabriz University of Medical Sciences, 2017)
Purpose: Nanostructured lipid carriers (NLCs) composed of solid lipid and oil are a new generation of lipid nanoparticles which have exhibited some merits over traditional used lipid nanoparticles in fortifying food and beverages and nutraceuticals delivery systems such as liposomes and solid lipid nanoparticles. Methods: In this study, Precirol and Compritol as solid lipids, Miglyol and Octyloctanoat as liquid lipids, Tween80, Tween20 and Poloxamer407 as surfactants were used to prepare vitamin D3-loaded NLC dispersion using hot homogenization method. The particle size and size distribution for all formulations were evaluated by immediately after production and during a storage period of 60 days. Results: The Precirol-based NLC showed superiority over Compritol-based NLC in the point of physical stability. Results clearly suggested that an optimum concentration of 3% of Poloxamer407 or 2% of Tween20 was sufficient to cover the surface of nanoparticles effectively and prevent agglomeration during the homogenization process. Octyloctanoat was introduced for the first time as a good substituent for Miglyol in the preparation of NLC formulations. The vitamin D3 Intestinal absorption enhanced by the incorporating in NLCs. Conclusion: It was concluded that NLC showed a promising approach for fortifying beverages by lipophilic nutraceuticals such as vitamin D.